Basketball coaches` utilization of ankle injury prevention strategies - McGuine, T. A.; Hetzel, S.; Pennuto, A.; Brooks, A. (Sports Health: A Multidisciplinary Approach, 2013)
Background: Ankle injuries are the most common high school basketball injury. Little is known regarding the utilization of ankle injury prevention strategies in high school settings.